设随机变量X的密度函数为[img=186x60]1802f2bf299fd10.png[/img]则E( 2X – 3 ) =( ).
A: -1
B: 1
C: 2
D: 4
A: -1
B: 1
C: 2
D: 4
A
举一反三
- 设随机变量X的密度函数为[img=186x60]18031e95a89688c.png[/img]则E( 2X – 3 ) =( ). A: -1 B: 1 C: 2 D: 4
- 设随机变量X的密度函数为[img=186x60]1803c07ad7ef54a.png[/img]则E( 2X – 3 ) =( ). A: -1 B: 1 C: 2 D: 4
- 设随机变量X的密度函数为[img=186x60]1802e8d42f03af2.png[/img]则E( 2X – 3 ) =( ). A: -1 B: 1 C: 2 D: 4
- 设随机变量X的密度函数为[img=186x60]180387de8bc0835.png[/img]则E( 2X – 3 ) =( ). A: -1 B: 1 C: 2 D: 4
- 设随机变量X的密度函数为[img=186x60]1802fe36aceccd0.png[/img]则E( 2X – 3 ) =( ). A: -1 B: 1 C: 2 D: 4
内容
- 0
设随机变量X的密度函数为[img=186x60]1802f2be7aa0462.png[/img]则E( 2X – 3 ) =( ). A: -1 B: 1 C: 2 D: 4
- 1
设随机变量X的密度函数为[img=186x60]1802f2bb0854ec8.png[/img]则E( 2X – 3 ) =( ). A: -1 B: 1 C: 2 D: 4
- 2
设随机变量X的密度函数为[img=186x60]1803395dc51e494.png[/img]则E( 2X – 3 ) =( ). A: -1 B: 1 C: 2 D: 4
- 3
设随机变量X的密度函数为[img=186x60]180380a165ee299.png[/img]则E( 2X – 3 ) =( ). A: -1 B: 1 C: 2 D: 4
- 4
设随机变量X的密度函数为[img=186x60]180387ddef1857c.png[/img]则E( 2X – 3 ) =( ). A: -1 B: 1 C: 2 D: 4